Manipulation of Neutrophils by Porphyromonas gingivalis in the Development of Periodontitis - Sochalska, Maja; Potempa, Jan (Frontiers in Cellular and Infection Microbiology, 2017)
The pathogenesis of the chronic periodontal disease is associated with a skewed host inflammatory response to periodontal pathogens, such as Porphyromonas gingivalis, that accounts for the majority of periodontal tissue damage. Neutrophils are the most abundant leukocytes in periodontal pockets and depending on the stage of the disease, also plentiful PMNs are present in the inflamed gingival tissue and the gingival crevice. They are the most efficient phagocytes and eliminate pathogens by a variety of means, which are either oxygen-dependent or -independent. However, these secretory lethal weapons do not strictly discriminate between pathogens and host tissue. Current studies describe conflicting findings about neutrophil involvement in periodontal disease. On one hand literature indicate that hyper-reactive neutrophils are the main immune cell type responsible for this observed tissue damage and disease progression. Deregulation of neutrophil survival and functions, such as chemotaxis, migration, secretion of antimicrobial peptides or enzymes, and production of reactive oxygen species, contribute to observed tissue injury and the clinical signs of periodontal disease. On the other hand neutrophils deficiencies in patients and mice also result in periodontal phenotype. Therefore, P. gingivalis represents a periodontal pathogen that manipulates the immune responses of PMNs, employing several virulence factors, such as gingipains, serine proteases, lipid phosphatases, or fimbriae. This review will sum up studies devoted to understanding different strategies utilized by P. gingivalis to manipulate PMNs survival and functions in order to inhibit killing by a granular content, prolong inflammation, and gain access to nutrient resources.